Effect of hot rotary swaging deformation on microstructure and properties of ASP30 grade powder metallurgical high speed steels strengthened by TiCN - CHEN Ze-min; ZHANG Qian-kun; XIAO Yi-feng; WU Liang; QIAN Jin-wen; LI Su-wang; TANG Jun (Fenmo yejin jishu)
The ASP30 powder metallurgy (PM) high speed steels strengthened by TiCN were fabricated by powder metallurgy process, the effects of TiCN and rotary awaging deformation on the mechanical properties, microstructure, and tribological behaviors of the ASP30 steels were investigated. The results show that, adding TiCN with the mass fraction of 5% can effectively improve the wear resistance of ASP30. After the quenching-tempering treatment, the bending strength of ASP30+5%TiCN with the 56% swaging deformation is 4084.99 N·mm‒2, and the impact toughness is 14.55 J·cm‒2. The strength and toughness of the ASP30 steels after swaging are effectively improved. After the repeated radial swaging deformation, the TiCN phases are obviously broken and distribute as the dispersion particles. Besides, the rotary swaging can promote the formation of TiCN core-rim structure and improve the wettability and bonding ability between the hard phase and the matrix, inhibiting the generation of cracks between the hard phase and the matrix during grinding.